Coastal Morphological Characteristics and Their Impact on Spatial Structure in Medan Belawan District - Prasetyo, Bima Hazril (Talenta Publisher, 2025)
This study explains the morphological characteristics that occur in the coastal area of ​​Belawan District. The Belawan coastal area experienced morphological changes in the form of changes in the coastline due to reclamation which was carried out in 2017, resulting in various phenomena such as abrasion and accretion on the Belawan coastline. This abrasion and accretion phenomenon also makes tidal flood disaster intervals in the Belawan sub-district more frequent. The tidal flood disaster had an impact on the spatial structure of the Belawan sub-district, such as damaged road and residential infrastructure, patterns of selecting industrial locations, warehousing, and service trade which avoided areas that had a high potential for flood disasters. This research seeks to determine the morphological characteristics of the Belawan coastal and the analytical method used in this research is descriptive analysis. The results of this research show that the characteristics of the Belawan coastal area have experienced changes originating from a combination of human and natural activities which have an influence on the spatial structure of Belawan District.